ARTIFICIAL INTELLIGENCE (AI) USAGE AMONG MALAYSIAN HIGHER LEARNING INSTITUTIONS: A STRUCTURED REVIEW ON THE ROLES AND IMPACT OF CHATGPT - Yusnilzahri , Nur Arifah Syahadah; Mohamad Rosman , Mohamad Rahimi; Saiful Bahry , Farrah Diana (Journal of Islamic, Social, Economics and Development, 2024)
ChatGPT, known as Chat Generative Pre-Trained Transformer, is the AI tool that was created by OpenAI that uses natural language processing to simulate real-time conversations with humans. The use of ChatGPT nowadays has increased in several years. ChatGPT has the potential to raise the level of student work significantly. It may benefit students in a variety of ways, including by offering helpful resources and information, assisting with language proficiency development, encouraging teamwork, enhancing time effectiveness and efficiency, and offering encouragement and support. However, there are several issues and difficulties associated with using ChatGPT in higher education. Researchers have expressed doubts about the accuracy and validity of the data provided by ChatGPT, alleging that it may contain manipulated or unreliable data. The findings show the advantages of using ChatGPT not only for students but also for lecturers and demonstrate ChatGPT's engagement in students' tasks. Therefore, the purpose of this study is to determine the impact of ChatGPT among students in higher education and to identify the factors influencing students to use ChatGPT. Structural Literature Review (SLR) was adopted to determine the purpose of the study. The conceptual framework was created to identify the factors influencing the use of ChatGPT among students.